Emphasizing the Role of Territorial Defense Forces of Ukraine in Bolstering Societal Resilience - Bohatyrets, Valentyna; Zoriy, Yaroslav (My University, 2023)
It should be articulated that in the context of unprovoked Russian-Ukrainian war, territorial defense forces proved to have played a vital role in bolstering societal resilience by safeguarding the security and stability of a nation. Consequently, Ukraine’s TDF’s top priority is to protect the territorial integrity of our country, defend its borders, and ensure the safety of Ukraine’s citizens. The current reality provided solid evidence that TDF’s role extends beyond traditional military operations, since they actively contribute to the resilience of our society in various ways. The authors’ focus revolves around the pivotal role of Ukraine's Territorial Defense Forces (TDF) in enhancing societal resilience within the country. Amidst historical conflicts and ongoing security threats, the TDF has emerged as a vital component of Ukraine's defense strategy. This article delves into the structure and functions of territorial defense forces, emphasizing their contributions to local security, rapid response, crisis management, national unity, and community resilience. By actively engaging citizens in defense efforts and providing comprehensive training and support, the TDF strengthens the bond between the state and its people, fostering a shared responsibility for national security.
Keywords: Territorial Defense Forces; societal resilience; local security; rapid response; national unity; Ukraine